KETAHANAN EKONOMI KELUARGA DALAM EKONOMI ISLAM: SEBAGAI UPAYA MENCARI SOLUSI ALTERNATIF - M. Ikhwan; Imroatus Solihah (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2021)
This paper explains the Islamic economic system which is believed to be not only an alternative economic system but can be a solution to various economic problems including the family economy. To explain this will explain the definition, genealogy and comparison of Islamic economics with conventional economic systems, and the last explained the Islamic economic solution to the economic resilience of the family economy. This paper uses a qualitative method to narrate the concept of Islamic economics as a solution to the family economy with a philosophical and normative approach and refers to secondary research sources such as books, journals and other scientific articles. From the observations that have been made, the economic resilience of the family starts from applying the Islamic economy in household life, then being simple/modest, abandoning usury practices, giving zakat, the spirit of work, avoid asking for solicitation and addressing the government properly.